Has climate change resulted in a mismatch between the spring arrival of the Common Cuckoo Cuculus canorus and its hosts in North Norway? - Barrett, Rob (Ornis Norvegica, 2014)
<!–[if gte mso 9]> <![endif]–>Analysis of spring arrival dates in North Norway showed advanced arrival of the Common Cuckoo Cuculus canorus but not of four of its most frequently used hosts. No evidence was found of a climate-driven mismatch that might contribute to the decline in the Norwegian Cuckoo population. <!–[if gte mso 9]> Normal 0 false false false NO-BOK X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>